Menstruation-related disseminated intravascular coagulation in an adenomyosis patient: case report and review of the literature. - Cernogoraz, Alice; Schiraldi, Luigi; Bonazza, Deborah; Ricci, Giuseppe (Gynecol Endocrinol, 2019)
Disseminated intravascular coagulation (DIC) is a high mortality coagulopathy that leads to simultaneous thrombotic and bleeding problems. It occurs as a complication in different disease as malignancies, obstetrical catastrophes, bacterial sepsis and traumas. We report on an extremely rare case of acute DIC in a patient with misdiagnosed adenomyosis and massive methrorragia which led to acute kidney failure. The patient was successfully treated with hysterectomy and blood product transfusions; however, a slight reduction of renal function persisted. We were able to confirm the cause-consequence link between adenomyosis and consumptive DIC since we saw the thrombi in the adenomyotic uterus from early hysterectomy specimen. Moreover, this is the first case, for the best of our knowledge, in which systemic consequences persist in an adenomyosis patient who developed a DIC. Early diagnose and treatment of acute DIC is essential for patient's survival and to prevent severe complications: adenomyosis should be kept in mind as a possible cause of DIC when a patient shows up with massive bleeding.

Meconium-stained amniotic fluid: a risk factor for postpartum hemorrhage. - Bouchè, Carlo; Wiesenfeld, Uri; Ronfani, Luca; Simeone, Roberto; Bogatti, Paolo; Skerk, Kristina; Ricci, Giuseppe (Ther Clin Risk Manag, 2018)
Background/aim: Clinical data with respect to the impact of meconium on the risk of maternal hemorrhage are scarce. Therefore, in this study, we aimed to determine whether meconium-stained amniotic fluid (MSAF) represents a risk factor for postpartum hemorrhage (PPH) after vaginal delivery in a large unselected population. Patients and methods: A retrospective cohort study evaluated 78,542 consecutive women who had a vaginal delivery between 24th and 44th weeks of gestation. The women who had undergone cesarean section were excluded to avoid possible bias. Postpartum blood loss was measured with graduated blood sack. Postpartum blood loss between 1,000 and 2,000 mL and >2,000 mL were classified as moderate and severe PPH, respectively. Results: A total of 74,144 patients were available for analysis. According to the color of amniotic fluid (AF), two groups of patients were identified: MSAF (n=10,997) and clear AF (n=63,147). The rates of severe and massive PPH were found to be significantly higher in the MSAF group than that of clear AF group (OR=1.3, 95% CI: 1.2-1.5, <0.001 and OR=2.5, 95% CI: 1.5-4.2, <0.001). Operative vaginal delivery rate was found to be higher in the MSAF group than that of clear AF group, but the difference was only borderline significant (OR=1.5, 95% CI: 1.0-2.2, =0.05). There were no significant differences between the MSAF and the clear AF groups with respect to episiotomies, second- or third-degree perineal tears, vaginal-perineal thrombus, cervical lacerations, vaginal births after cesarean section, twin deliveries, and placental retention rates. Conclusion: To the best of our knowledge, this is the first clinical study that has investigated the role of MSAF as a risk factor for PPH after vaginal delivery in an unselected population. Our results suggest that MSAF is significantly associated with higher risk of moderate and severe PPH than clear AF.

Medical treatments for endometriosis-associated pelvic pain. - Zito, Gabriella; Luppi, Stefania; Giolo, Elena; Martinelli, Monica; Venturin, Irene; Di Lorenzo, Giovanni; Ricci, Giuseppe (Biomed Res Int, 2014)
The main sequelae of endometriosis are represented by infertility and chronic pelvic pain. Chronic pelvic pain causes disability and distress with a very high economic impact. In the last decades, an impressive amount of pharmacological agents have been tested for the treatment of endometriosis-associated pelvic pain. However, only a few of these have been introduced into clinical practice. Following the results of the controlled studies available, to date, the first-line treatment for endometriosis associated pain is still represented by oral contraceptives used continuously. Progestins represent an acceptable alternative. In women with rectovaginal lesions or colorectal endometriosis, norethisterone acetate at low dosage should be preferred. GnRH analogues may be used as second-line treatment, but significant side effects should be taken into account. Nonsteroidal anti-inflammatory drugs are widely used, but there is inconclusive evidence for their efficacy in relieving endometriosis-associated pelvic pain. Other agents such as GnRH antagonist, aromatase inhibitors, immunomodulators, selective progesterone receptor modulators, and histone deacetylase inhibitors seem to be very promising, but there is not enough evidence to support their introduction into routine clinical practice. Some other agents, such as peroxisome proliferator activated receptors-γ ligands, antiangiogenic agents, and melatonin have been proven to be efficacious in animal studies, but they have not yet been tested in clinical studies.
Keywords: Endometriosis; Female; Gonadotropin-Releasing Hormone; Histone Deacetylase Inhibitors; Hormone Antagonists; Humans; Pain Management; Pelvic Pain; Progestins

Management of the adnexal mass. - Ricci, Giuseppe; Zito, Gabriella; Fischer-Tamaro, Leo (Obstet Gynecol, 2011)
Keywords: Female; Humans; Ovarian Neoplasms